2014
DOI: 10.1109/tdei.2014.6832266
|View full text |Cite
|
Sign up to set email alerts
|

Factors of influence on surface erosion of epoxy resin exposed to electrical discharges

Abstract: This paper investigates the influence of electrical as well as environmental stresses on surface erosion of polymeric materials used in high voltage insulation. The analyzed electrical stresses are applied voltage magnitude and frequency; whereas the environmental stresses of concern are temperature and humidity of air above sample surface. Suitable electrode arrangement is chosen in order to produce measurable erosion and guarantee the control of the analyzed stressing factors. Discharge intensity is defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Effect of relative humidity and subsequent application of corona was carried out and significant reduction in the surface resistivity was observed. Similarly a single needle-plate arrangement with tangential electrical stress has been used in [16], to accurately study the environmental factors on discharge intensity and the erosion of the material. With the advent of HVDC transmission lines and usage of polymeric insulators for HVDC applications, effort has been made in the literature [10,13,17] to study the effect of DC corona.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of relative humidity and subsequent application of corona was carried out and significant reduction in the surface resistivity was observed. Similarly a single needle-plate arrangement with tangential electrical stress has been used in [16], to accurately study the environmental factors on discharge intensity and the erosion of the material. With the advent of HVDC transmission lines and usage of polymeric insulators for HVDC applications, effort has been made in the literature [10,13,17] to study the effect of DC corona.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the influence of negative DC on the degradation is more in comparison with positive DC. In the above cited literature, experiments were conducted in dry air condition [5,8,10], with high relative humidity [4,6,12,14], in open air condition [7,15], and under controlled environment [16]. However, the literature on the corona degradation effect under the influence of moisture or effect due to cold fog is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Mostafa Refaey [8] was investigated that partial discharge intensity is dependent on the magnitude of the test voltage and reaches significant level at higher voltages. His observation was actually expected from the equation used to calculate these quantities, where energy is dependent on the test voltage.…”
Section: Figure 6 Graphic Of Leakage Current Under Wet and Dry Testmentioning
confidence: 99%
“…[6]. Corona induced degradation has been one of the topics of research since the polymer insulators are being used in service [7][8][9][10][11][12]. Polymeric insulators when subjected to the corona discharges, lead to loss of hydropobhicity, crack formation, hydroxylation and surface oxidation etc.…”
Section: Introductionmentioning
confidence: 99%